Fabrication of high-concentration Cu-doped deuterated targets for fast ignition experiments. (1st January 2023) - Ikeda, Tomokazu; Kaneyasu, Yumi; Hosokawa, Hitomi; Shigemori, Keisuke; Norimastu, Takayoshi; Cadatal-Raduban, Marilou; Nagai, Keiji; Kojima, Sadaoki; Abe, Yuki; Miura, Eisuke; Kitagawa, Yoneyoshi; Takemura, Mao; et al.
Abstract: In high-energy-density physics, including inertial fusion energy using high-power lasers, doping tracer atoms and deuteration of target materials play an important role in diagnosis. For example, a low-concentration Cu dopant acts as an x-ray source for electron temperature detection while a deuterium dopant acts as a neutron source for fusion reaction detection. However, the simultaneous achievement of Cu doping, a deuterated polymer, mechanical toughness and chemical robustness during the fabrication process is not so simple. In this study, we report the successful fabrication of a Cu-doped deuterated target. The obtained samples were characterized by inductively coupled plasma optical emission spectrometry, differential scanning calorimetry and Fourier transform infrared spectroscopy. Simultaneous measurements of Cu K-shell x-ray emission and beam fusion neutrons were demonstrated using a petawatt laser at Osaka University.